2010
DOI: 10.1590/1808-1657v77p6512010
|View full text |Cite
|
Sign up to set email alerts
|

Produção semissólida de Metarhizium anisopliae e Beauveria bassiana em diferentes substratos e efeito da radiação ultravioleta e da temperatura sobre propágulos desses entomopatógenos.

Abstract: RESUMO O trabalho teve os seguintes objetivos: 1) avaliar diferentes substratos para a produção semissólida dos fungos Metarhizium anisopliae e Beauveria bassiana; 2) verificar a tolerância dos conídios produzidos ao efeito da radiação ultravioleta e da temperatura; e 3) avaliar a patogenicidade dos conídios a Diatraea saccharalis. Para ambos os fungos, foram utilizadas 6 repetições para cada tratamento: amido de milho, arroz integral, arroz parboilizado tipo1, arroz tipo 1 e 2, aveia em flocos, canjiquinha, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
(1 reference statement)
0
3
0
1
Order By: Relevance
“…Viability tests applied to products based on aerial conidia deriving from B. bassiana IBCB66 recorded viable aerial conidia rates ranging from 85.5% to 90%, whereas mean colony forming units at blastospores' concentration of 2.33 × 10 6 was in compliance with indices indicating microorganism efficiency, based on OTTATI- DE-LIMA et al (2010).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Viability tests applied to products based on aerial conidia deriving from B. bassiana IBCB66 recorded viable aerial conidia rates ranging from 85.5% to 90%, whereas mean colony forming units at blastospores' concentration of 2.33 × 10 6 was in compliance with indices indicating microorganism efficiency, based on OTTATI- DE-LIMA et al (2010).…”
Section: Resultsmentioning
confidence: 96%
“…The blastospore suspension treatment recorded decreased bored fruit rates in comparison to treatments with rice conidia + fungus powder. Results recorded by OTTATI- DE-LIMA et al (2010) have indicated that blastospores have caused Diatraea saccharalis mortality rate ranging from 26% to 29% for M. anisopliae and B. bassiana in the assessed media, respectively. Blastospores' resistance in the environment is quite low due to the sensitivity of its hyphal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foram estudados vários outros substratos naturais para a produção de fungos por fermentação sólida, tais como: milho e trigo em grão, farelo de trigo, fubá de milho, vários tipos de arroz (1, 2 e quirela), arroz parboilizado, entre outros, porém o arroz parboilizado ou o tipo 1 foram sempre os mais eficientes e com melhor custo-benefício (Ottati- de-Lima, et. al.…”
Section: Preparo Do Meio De Cultura Para Grande Escalaunclassified